The challenge of moving to a Common Consolidated Corporate Tax Base in the EU - Tobias Hentze (Institut der deutschen Wirtschaft (IW), 2019)
The introduction of a Common Consolidated Corporate Tax Base (CCCTB) in the European Union (EU) would substantially change the rules of the game in international taxation. According to the proposal by the European Commission (EC), the profits of a Multinational Enterprise (MNE) would no longer be assessed by using the arm's length principles and (hypothetical) market prices, but split based on a formulary apportionment. This implies that an allocation key consisting of sales volume, number of employees and capital invested would be applied to distribute the taxable profits of an MNE. From an economic perspective, the principle of taxing profits at source would be thereby abolished. However, due to the current difficulty for taxpayers and tax authorities to agree on adequate transfer prices, a radical change as proposed by the EC might be reasonable. Hence, the EC proposal for the CCCTB is a promising goal as it could lower the red tape burden for MNE as well as tax authorities. Furthermore, the adjustment of the debt bias and the encouragement of R&D as additional items of the EC proposal could stimulate economic growth. A main obstacle for the implementation of a CCCTB would be the expected shifts in tax revenue which make a political agreement at the EU level very difficult. The application of a CCCTB would substantially redistribute corporate profits among the EU member states as a simulation by the German Economic Institute (IW) shows. Especially, Ireland, Luxembourg and Malta would receive significantly less tax revenue since sales volume, number of employees and capital invested are relatively small in these countries. France and Italy, in contrast, would be on the winning side. Germany would also benefit even though to a rather low degree. A main reason for this result is that the strongly exporting German corporations today pay a large proportion of their corporate taxes in Germany. With the application of the CCCTB, parts of the taxable profits would be allocated to foreign countries. From a systematic point of view, the CCCTB is only convincing if there is a global commitment. A simulation of the tax revenue effects for the G20 countries when applying a CCCTB shows that the shift would also be drastic. The EU member states - even the big ones - would have to accept lower taxable corporate profits. Instead, the United States could increase the corporate tax base mainly because of the high consumption level. China and India would benefit due to the large number of employees. Thus, whether a country ranks among the winners or losers in terms of tax revenue depends foremost on the peer group.
Keywords: H25; H26; 330